2015
DOI: 10.1007/s11886-015-0562-3
|View full text |Cite
|
Sign up to set email alerts
|

Change in Daily Ambulatory Activity and Cardiovascular Events in People with Impaired Glucose Tolerance

Abstract: Patients with pre-diabetes have a tenfold higher risk of developing Type 2 DM and a twofold higher risk of developing coronary heart disease compared to non-diabetics. Interventions targeted at those in an early stage of impaired glucose metabolism can delay or prevent diabetes. Effects of these interventions on cardiovascular outcome are unknown. This article aims to review current and available data on lifestyle intervention, specifically physical activity, on cardiovascular outcomes in populations at risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In nonThal populations, regular physical activity has been shown to decrease depression and improve mood 7 , school performance 8,9,10 , glucose tolerance 11,12,13 , weight maintenance 14 , body composition 15 and bone health 16,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In nonThal populations, regular physical activity has been shown to decrease depression and improve mood 7 , school performance 8,9,10 , glucose tolerance 11,12,13 , weight maintenance 14 , body composition 15 and bone health 16,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Impaired glucose tolerance (IGT) is considered a pre stage of the onset of T2DM and this stage has the typical characteristics of insulin resistance. Several clinical studies had confirmed the increased risk of coronary artery disease (CAD) in patients with IGT [3,4]. Insulin resistance could explain the increased risk for CAD in patients with IGT because insulin resistance is associated with IGT and postprandial hyperglycemia [5].…”
Section: Introductionmentioning
confidence: 99%